A redescription of the ant mimicking spider Myrmecium gounellei (Araneae: Corinnidae, Castianeirinae), with notes on the genus - Marusik, Yuri M.; Omelko, Mikhail M.; Koponen, Seppo (Zootaxa, 2015)
Myrmecium Latreille, 1824 is a relatively large genus of Castianeirinae with 16 species, distributed exclusively in the Neotropics (WSC 2015). Although this genus is rather well known as a good example of ant mimicking spiders, its taxonomy is very poorly studied. Two of its species are described based on unknown sex; one species is described based on a juvenile; eight species are known based on a single sex: for seven, only females are known, and for one, only a male is known (Platnick 2014). Eleven species are known from a single record, and two species were never illustrated. The latest taxonomic paper dealing with Myrmecium was published more than 60 years ago by Camargo (1953). Although both sexes are known for six species of Myrmecium, the male palp and female epigyne are illustrated for three species only. The male palp is relatively well illustrated for the type species of the genus, M. rufum Latreille, 1824 (Camargo 1953). Somatic characters are illustrated also only for M. rufum (Simon 1897).